Logistics in computer integrated construction framework - Akbaş, Ragıp. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Sciences and Engineering, 1997., 1997)
Infonnation technology implementation in construction witnessed maj or progress in recent years. Hardware and software technology improvements allowed computer use in most of the companies. However there is still much to go to achieve effective and integrated infonnation systems and gain real benefits. Similarly logistics concept, evolved from manufacturing materials management and distribution gains much more importance because of globalization of the world, reduced time to market and customer driven approach. Effective integration of these vital concepts will undoubtedly reveal highly efficient construction. This study particularly investigates construction logistics from infonnation technology point of view considering the current and future trends. Following the recent literature survey to present computer integrated construction idea, an integrated logistics concept in construction is explained. Then a reference data model of construction logistics for construction enterprises is proposed. This model is partially implemented using a relational database management system and object oriented development environment. A case study in a process plant construction is developed to demonstrate the concepts developed throughout the study.
Keywords: Computer integrated manufacturing systems.; Integrated logistic support.